Systemic hyperfibrinolysis after trauma: a pilot study of targeted proteomic analysis of superposed mechanisms in patient plasma. Issue 6 (June 2018) - Banerjee, Anirban; Silliman, Christopher C.; Moore, Ernest E.; Dzieciatkowska, Monika; Kelher, Marguerite; Sauaia, Angela; Jones, Kenneth; Chapman, Michael P.; Gonzalez, Eduardo; Moore, Hunter B.; D'Alessandro, Angelo; Peltz, Erik; et al.
Abstract : BACKGROUND: Viscoelastic measurements of hemostasis indicate that 20% of seriously injured patients exhibit systemic hyperfibrinolysis, with increased early mortality. These patients have normal clot formation with rapid clot lysis. Targeted proteomics was applied to quantify plasma proteins from hyperfibrinolytic (HF) patients to elucidate potential pathophysiology. METHODS: Blood samples were collected in the field or at emergency department arrival and thrombelastography (TEG) was used to characterize in vitro clot formation under native and tissue plasminogen activator (tPA)-stimulated conditions. Ten samples were taken from injured patients exhibiting normal lysis time at 30 min (Ly30), "eufibrinolytic" (EF), 10 from HF patients, defined as tPA-stimulated TEG Ly30 >50%, and 10 from healthy controls. Trauma patient samples were analyzed by targeted proteomics and ELISA assays for specific coagulation proteins. RESULTS: HF patients exhibited increased plasminogen activation. Thirty-three proteins from the HF patients were significantly decreased compared with healthy controls and EF patients; 17 were coagulation proteins with anti-protease consumption ( p < 0.005). The other 16 decreased proteins indicate activation of the alternate complement pathway, depletion of carrier proteins, and four glycoproteins. CXC7 was elevated in all injured patients versus healthy controls ( p < 0.005), and 35 proteins were unchanged across all groups ( p > 0.1 and fold change of concentrations of 0.75–1.3). CONCLUSION: HF patients had significant decreases in specific proteins and support mechanisms known in trauma-induced hyperfibrinolysis and also unexpected decreases in coagulation factors, factors II, X, and XIII, without changes in clot formation (SP, R times, or angle). Decreased clot stability in HF patients was corroborated with tPA-stimulated TEGs. LEVEL OF EVIDENCE: Prognostic, level III. Abstract : Supplemental digital content is available in the text.